Estimating the prevalence of stress among Indian students during the COVID-19 pandemic: A cross-sectional study from India. Issue 2 (April 2021) - Chhetri, Bijoy; Goyal, Lalit M.; Mittal, Mamta; Battineni, Gopi
الملخص: أهداف البحث: منذ ديسمبر ٢٠١٩، شكل وباء كوفيد-١٩ تهديدا كبيرا مع ارتفاع عدد الوفيات، والعدوى، ومخاطر الإجهاد النفسي. تأثر عدد كبير من الطلبة بسبب الاستراحة الطويلة من النشاطات الأكاديمية والجلوس في البيت. محور هذه الدراسة هو فهم مستوى التوتر عند الطلاب في الهند، واختلال التوازن النفسي، والعقبة الرئيسة خلال الإغلاق الكامل بسبب كوفيد-١٩. طرق البحث: باستخدام طريقة أخذ عينات كرة الثلج. تم إجراء مسح عبر الإنترنت لمقياس الإجهاد المتصور على الطلاب عبر الهند. مع التفاصيل الديموغرافية، سجل المشاركون أيضا عن أنماط الدراسة والتحديات خلال فترة الإغلاق. تم حساب الدرجات الإحصائية للردود وتحليل المتغيرات الديموغرافية. تم مقارنة مستوى مقياس الإجهاد وأجريت تحليلات التباين والانحدار. النتائج: لاحظنا أن الطلاب كانوا خلال الإغلاق والجائحة متوترين بشكل عام. وكان الإناث (المتوسط =٣.٠٣) متوترات أكثر من الذكور (المتوسط =٢.٦١) حيث إنهم كانوا تحت الضغط باستمرار بسبب أحداث الحياة المجهدة. الاستنتاجات: خلال الجائحة، يجب مراقبة صحة الطلاب العقلية بشكل مستمر لأنهم متوترون من الخوف حول دراستهم ومستقبلهم الوظيفي. Abstract: Objective: Since December 2019, the COVID-19 pandemic has posed a substantial threat with its associated high mortality, infection, and risk of psychological stress. A large number of students are affected because of a prolonged break from academic activities and staying at home. The focus of this study is to understand the stress levels of Indian students, any psychological imbalances, and their major hurdles during the COVID-19 lockdown. Methods: Using a snowball sampling method, an online survey of the Perceived Stress Scale (PSS) was conducted on students across India. Along with their demographic details, the participants also reported their study patterns and challenges during their confinement period. The statistical scores for the responses were calculated and the demographic variables analysed. The levels indicated by the PSS were compared, and variance and regression analyses were performed. Results: We observed that students were generally stressed during lockdown and the pandemic. Females (mean = 3.03) were more stressed than males (mean = 2.61) as they were constantly under pressure because of stressful life events (OR = 0.752, 95% CI = 2.425–310.642) and apprehensive about their studies (RII = 0.67, OR = 2.168, 95% CI = 0.332–6.691). Conclusion: During the pandemic, students' mental health needs to be continually monitored as they are stressed owing to fear as well as about their studies and future careers.